LEARNING STRATEGIES APPLIED BY SUCCESSFUL EFL LEARNERS IN SPEAKING - Mbani , Nurmakfira; Kamaruddin, Abdul; Mashuri, Mashuri; Rofiqoh, Rofiqoh (e-Journal of ELTS (English Language Teaching Society), 2023)
Research objectives describe what researchers want to achieve through research. This research will apply a qualitative descriptive design. Therefore, to find out the learning strategies applied by successful speaking students, the subjects in this research were students of Tadulako University, Faculty of Teacher Training and Education, class C English Education 2018. This research aims to determine the learning strategies used by successful EFL students in speaking English. The subject of this research is students who get grades B+ to A in speaking four; 15 participants were obtained from DPNA and used the purposive sampling technique, and respondents who had good answers continued to the interview stage. This interview stage uses a snowball sampling research technique. Data collection uses a google forms questionnaire and interviews. As for the strategies, There are five strategies that the researcher obtained through interviews and from the 15 statements in the questionnaire, two strategies became the dominant strategy used. The highest percentage was 2 with 60% results, and other questions were brought from 60%